Intertextuality and Mise en Abyme in Nobuhiro Suwa’s H Story and A Perfect Couple. Between European Modernity and Japan - Miguel Muñoz-Garnica (Arts, 2018)
Nobuhiro Suwa, often called “the most French of Japanese directors”, has a complex relationship with European cinematic modernity. His two feature films H Story (2001) and A Perfect Couple (2005) can provide useful case studies, as they were created in dialogue with two key references of that modernity: Hiroshima mon amour (1959, Alain Resnais) and Journey to Italy (Viaggio in Italia, 1954, Roberto Rossellini), respectively. Both films tend to confront and gloss their previous pairs, but they are also continuations of their concerns and their aesthetical discoveries. The presence of intertextuality elements connecting those films, as well as the use of myse en abyme structures are deeply analyzed in this article to attain a greater understanding on how this process of transcultural dialogue works. Besides, both films exemplify different ways of developing the references on which they are built, namely deconstruction for H Story and reconstruction for A Perfect Couple.